Overworked Families - Suzanna Smith (EDIS, 2012)
“Most weeks, as I breathlessly try to keep up with my family responsibilities and the demands of my job, I often lament, ‘There just aren’t enough hours in the day!’” This 2-page Family Album Radio transcript was written by Suzanna Smith and published by the UF Department of Family, Youth and Community Sciences, August 2012.